Nurturing Faith and Character: A Values-Based Approach to Islamic Religious Education in Vocational High Schools - Rohmat Mulyana; Fuad Hilmi; Busro Busro; Mohamad Jaenudin (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to explore the implementation of values education in Islamic religious education at a Vocational High School. The research utilized a descriptive qualitative method and purposive sampling to select school principals, student affairs, Islamic Religious Education Teachers, and students as research subjects. The data collection techniques involved observation, interviews, and documentation. The findings indicated that values education implemented at SMK Syahida led to students who are devout in worship, democratic, environmentally aware, and tolerant. The results were verified with a data assessment rubric, which showed that values education at SMK Syahida was integrated into Islamic religious education. This research concludes that Islamic religious education is suitable for implementing values education. The implications and benefits of this research include contributing to the development of Islamic religious education and values education in Indonesia. The novelty of this research is the integration of values education into Islamic religious education in vocational schools.